DAMPAK INVESTASI ASING LANGSUNG OLEH PT BENING BIG TREE FARMS TERHADAP EKONOMI POLITIK PETANI GARAM KLUNGKUNG - Cahyadi, I Dewa Nyoman Ngurah Ari; Dharmiasih, Wiwik; Fasisaka, Idin (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL), 2014)
This research aims to describe the impact of foreign direct investment PT Bening Big Tree Farms in Klungkung regency. Klungkung is one of the regencies in Bali that has a traditional salt processing industry for the region of East Bali . The influx of foreign investment by PT Bening Big Tree Farms has made Klungkung now not only have the traditional salt processing industry , but also the modern salt processing industry . Klungkung able to do so because the policy of regional autonomy that has been applied in Indonesia in 1999. In this research, writer use the concept of regional autonomy and foreign direct investment .